EXAMINING THE CITIZEN SATISFACTION IN NEW SAKPOLE: INSIGHTS FROM THE TECHNOLOGY ACCEPTANCE MODEL - Irma Yunita; Ari Subowo; Mohammad Nurul Huda (Dialogue : Jurnal Ilmu Administrasi Publik, 2025)
E-government represents a governmental adaptation aimed at enhancing digital public service. The Regional Revenue Management Agency (Bapenda) of Central Java Province has developed an e-government application called New Sakpole, designed to facilitate online motor vehicle tax payments for the public. However, the application has been perceived as presenting challenges, such as difficulties in use and limited utility, leading to dissatisfaction. This study examined the relationship between perceived ease of use and perceived usefulness on user satisfaction with the New Sakpole application for motor vehicle tax payments in Central Java. Employing a quantitative approach, primary data were collected from 100 respondents and analysed using Spearman's rank correlation and multiple regression analysis. The findings indicate a significant positive relationship between perceived ease of use and user satisfaction, with a 59.7% contribution to the model. Perceived usefulness also showed a positive and significant correlation with satisfaction, contributing 41.2%. Simultaneous analysis of the two variables further demonstrated a significant positive relationship of 68.3%. The study concluded that all tested variables exhibited a positive and significant relationship, underscoring the importance of perceived ease of use and usefulness as key indicators for enhancing user satisfaction. The more accessible and beneficial an application is, the higher the level of user satisfaction.